The Use of High Order Thinking Skill in Story Telling Method in Order to Improve Children' Critical Thinking - Aisyah, Siti; Setiawan, Denny (English Education Department, Universitas Islam Indonesia, 2009)
Children need to be equipped with the ability to navigate the world and to think independently, not just recite facts. One of the thinking ability dimensions is creating thinking associated with the ability to explore ideas, conclude possibilities, and find correct answers more than one answer. In this era of globalization and advances in technology, where changes rapidly occur in community, creative thinking ability is a need for every human being who want to succeed in a variety of competitions. Therefore, the ability to think creatively should be given since the age of early childhood.One way to develop critical and creative thinking is to give children experiences in thinking critically and creatively and it is known as high order thinking skills (HOTS). As basic of developing HOTS we can learning domains created by Benjamin Bloom. Accordingly there are three domains, these are cognitive, effective, and psychomotorIn Kindergarten level, to train high order thinking to children is through joyful activities and not through hard thinking exercices and it is satisfying kindergarten motto that is learn by playing and play while learning. One of joyful activities for children in which we can develop high order thinking skills is story telling. A structured and systematic story telling activity is story telling method, This method has been broadly used in many kindergarten because naturally there is no child who doesn't like a story. The purpose of this method generally is to develop language aspect of children development. However, other aspects can also be developed in line with the development of language, one of them is cognitive aspectUsually, story telling method is attributed by ask and answer activities that can take place before, while, and after story telling. In this activities teacher ^k the children what they have heard to check their understanding. .Sometimes, the teacher ask them about the story before the story is delivered to them. This strategy is to train them to predict a story by thinking about the title of the story. However, observations to some kindergarten classes - showed that most of the teachers questions were about remembering something rather than asking them to think critically. This paper will describe how teacher can make children think creatively and critically by using High Order Thinking Skills (HOTS) questions in a story telling activity.